Trataka Karma and Eye Health: Ancient Practice, Modern Relevance - Sharma, Ekta; Thakur, Shalini (International Research Journal of Ayurveda & Yoga, 2025)
Trataka Karma is one of the Shatkarma practices mentioned in Yogic literature, and it holds an important place in both ocular and mental health traditions of ancient India. Ayurveda considers the Netra (eye) a highly delicate sense organ, governed primarily by Alochaka Pitta and nourished by all seven Dhatus. Imbalance of Doshas, especially due to overuse, misuse, or excessive strain, leads to visual disturbances such as Timira, which begins with blurred or unclear vision. Yoga provides complementary practices to purify and strengthen both the eyes and the mind. Among these, Trataka Karma, steady gazing without blinking until tears naturally flow, is described in texts such as the Hatha Yoga Pradipika and Gheranda Samhita as beneficial for cleansing the eyes, improving concentration, and calming mental restlessness. This review compiles references from classical Ayurvedic and Yogic sources, including the Rigveda, Upanishads, Charaka Samhita, Sushruta Samhita, Ashtanga Hridaya, Hatha Yoga Pradipika, and Gheranda Samhita, along with modern scientific insights. The conceptual basis of Trataka Karma is explored through the lens of Netra Sharira, Dosha dynamics, and Yogic purification techniques. Modern correlations, such as accommodation exercise, tear-film stability, relaxation response, and attention enhancement, help validate the classical claims. With digital eye strain, myopia, and mental stress rising globally, Trataka Karma emerges as a safe, inexpensive, and practical preventive tool. Its enduring relevance demonstrates the wisdom of integrating ancient holistic knowledge with contemporary wellness needs.